Native-speakerism and professional teacher identity in L2 pronunciation learning - Alghazo, Sharif; Zidan, Mahmoud (Universitas Pendidikan Indonesia, 2019)
Many studies in different contexts have examined both English as a second language (ESL) and English as a foreign language (EFL) students’ convictions about the connection between nativeness in English and professional teacher identity; however, very few studies solely focused on that connection in second language (L2) pronunciation teaching. This paper explores EFL university students’ experiences in learning English pronunciation from ‘native’- and ‘nonnative’- English-speaking teachers (NESTs and NNESTs). Based on an empirical study of undergraduates-prospective English language teachers-at the University of Jordan, the paper finds that most students still view ‘nativeness’ as the main descriptor of effective teaching, strongly believing NESTs to be the ‘authority’ and source of ‘correctness,’ both of which convictions are emblematic of native-speakerism, which in turns leads to both cultural panic and voicelessness on the part of NNESTs and learners. The study concludes with calling for the need to raise awareness among EFL students of the various manifestations of English as a global language-particularly the irrelevance of nativeness to effective teaching-and incorporating NNESTs into teaching L2 pronunciation and rejecting their marginalisation in teaching pronunciation in EFL contexts.